2016
DOI: 10.21009/econosains.0142.03
|View full text |Cite
|
Sign up to set email alerts
|

Evaluasi Program Ujian Nasional (Un) Pada SMK Negeri Di Jakarta Selatan

Abstract: This study aims to determine Evaluation Program of the National Examination (UN) in the State Vocational School in South Jakarta. This study includes qualitative research, where research in SMK who has the Office Administration Program in South Jakarta, which contained 10 SMKN. The resources are empirically Principal and Chairman of the Program Office Administration. Collecting data using the method of observation, interviews, documentation and archive footage, while the analysis of data using qualitative data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Menurut Henry Eryanto (Eryanto et al, 2016), evaluasi program ialah susunan kegiatan yang dikerjakan dengan terencana serta teliti guna mengenali tingkatan keterlaksanaan atau kesuksesan suatu program. Karena itu, program pembelajaran yang dirancang oleh guru demi tujuan yang akan dicapai, diketahui berhasil atau tidaknya tujuan program pembelajaran maka diperlukan evaluasi program pembelajaran.…”
Section: Pendahuluanunclassified
“…Menurut Henry Eryanto (Eryanto et al, 2016), evaluasi program ialah susunan kegiatan yang dikerjakan dengan terencana serta teliti guna mengenali tingkatan keterlaksanaan atau kesuksesan suatu program. Karena itu, program pembelajaran yang dirancang oleh guru demi tujuan yang akan dicapai, diketahui berhasil atau tidaknya tujuan program pembelajaran maka diperlukan evaluasi program pembelajaran.…”
Section: Pendahuluanunclassified
“…Therefore, from 2015 until 2019 as the latest National Examination held by the government, its function is changing, being a tool to drawing the quality of education in Indonesia. Various literature studies that have been conducted found that there is a controversy that occurs among the community related to the government policy in implementing the national examination, even among the policymaker [6]. The controversy is divided into two versions.…”
Section: Introductionmentioning
confidence: 99%
“…For the past five years, the government has continued to work on improving national examinations and developing the newest instrument of national examination using a computer equipped with specific software to display questions and answer processes with the same level of difficulty as paper-based national examination [8], which is known as UNBK 6 to reduce budgets and reduce fraud. It is right that UNBK implementation model directly or indirectly provides benefits, including saving duplication costs, facilitating the distribution of materials, quickly reaching all regions, high security, easy scoring process, and make it easier to print certificates of national examination results [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation